Pelatihan dan Bantuan Sarana Usaha Bagi Pelaku Usaha Mikro Produk Krupuk Kedelai Desa Menturus, Kec. Kudu, Kab. Jombang - Rahayu Rahayu; Rini Armin (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Training activities and assistance with business facilities is one of the programs of the Jombang Regency Social Service, this activity is intended for participants of the Family Hope Program (PKH), while the aim to be achieved from this activity is to increase household income. The target of this program is to help overcome problems in the businesses of PKH Program beneficiary groups, including product innovation, use of technology and assistance with facilities to increase the quantity and quality of production so that sales turnover increases. Method kThis service activity was carried out by providing training to PKH program participants in Menturus Village, Kec. Kudu, Kab. Jombang. Training activities using practical methods for making various soy-based cracker products and various flavor variants (spicy, balado, original onion and fruit flavors), production techniques using lecture methods to deliver material on marketing strategies for new products accompanied by workshops on strategy applications for entering new markets, and direct questions and answers, as well as the practice of making soybean crackers